2021
DOI: 10.2478/bhk-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lower limb plyometric and resistance training on the stiffness of Achilles and patellar tendons in recreational athletes

Abstract: Study aim: This study aimed to investigate the influence of combined plyometric and resistance training of lower limbs when administered for a shorter duration of six weeks on the stiffness of Achilles and patellar tendons as well as the jump height. Materials and methods: Twenty recreational athletes were administered six weeks of a single session of lower limb resistance training and one session of plyometric training every week for a total duration of six weeks. Tendon stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Literature studies reporting MyotonPro assessment of the patella tendon have primarily recruited athletes, for whom the stiffness values might be elevated. However, neglecting elite athlete studies and considering control groups, mean values have been reported ranging from 780 to 900 N/m, 7 , 60 consistent with the present study’s results.…”
Section: Discussionsupporting
confidence: 91%
“…Literature studies reporting MyotonPro assessment of the patella tendon have primarily recruited athletes, for whom the stiffness values might be elevated. However, neglecting elite athlete studies and considering control groups, mean values have been reported ranging from 780 to 900 N/m, 7 , 60 consistent with the present study’s results.…”
Section: Discussionsupporting
confidence: 91%
“…Our study (Figures 3, 4) and previous studies reported MDCs for PT and AT stiffness and length measurements using the myotonometry method (12,13,15) and the EFOV-US technique (19,20), respectively. With regard to the results of previous studies investigating changes in PT and AT stiffness (31,(48)(49)(50)(51)(52)(53) and length (34, 36-38, 43, 44, 54) in sports and medicine, these changes could be detected outside the measurement error using myotonometry and the EFOV-US technique, which supports the practical applicability of both technologies. For future studies using the EFOV-US technique, and as conducted here, we recommend the usage of a fixable brace to avoid axial shifts of the US probe.…”
Section: Clinical and Practical Implicationssupporting
confidence: 65%
“…In the process of constructing a prediction model for body parts that are vulnerable to damage during strenuous exercise, the intrinsic relationship between the attributes of sports injuries and the motion amplitude of body parts is first obtained. 5 We construct the relationship equation between the part that reflects the sports injury and the movement amplitude of the body part. Calculate the variable between the attributes of severe sports injury and the movement range of vulnerable body parts.…”
Section: Predictive Modeling and Simulation Of Vulnerable Parts Of Th...mentioning
confidence: 99%